IMMUNOHISTOCHEMICAL EXPRESSION OF PD-L1 IN NON-SMALL CELL LUNG CARCINOMA - Khan, Muhammad Umair; Hafeez ud Din,; Wajahat Ahmed Khan, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Lung cancer is a leading cause of death related to cancer worldwide, surpassing the number of deaths caused by breast, colon and prostate cancers. Objective of the study was to determine the frequency immunohistochemical expression of PD-L1 in non-small cell lung carcinoma (NSCLC). It was a descriptive cross-sectional study, carried out at the Department of Histopathology, Armed Forces Institute of Pathology, Rawalpindi, from January 2020 to July 2021. Methods: We inducted total of 145 diagnosed cases of NSCLC irrespective of age, gender, histological grade and stage of carcinoma. Immunohistochemical staining of PD-L1 was done using Leica kit. Patients with no expression for PD-L1 were considered negative, whereas immunohistochemical expression of ‰¥1% is considered positive. PD-L1 statuses of all patients was determined. The data was analyzed by using SPSS version 25. Results: In our study age ranges from 31 to 85 years with mean age of 64.20±10.90 years. Out of the 145 patients, 126 (86.90%) were male and 19 (13.10%) were females. 108 (74.50%) were squamous cell carcinoma and 37 (25.50%) were adenocarcinoma. Most of them were histological grade II, 88 (60.70%), followed by grade I in 26 (17.9%). Immunohistochemical expression of PD-Ll in NSCLC was found in 35 (24.13%) patients. Of all the positive cases, PD-L1 expression was slightly higher in adenocarcinoma 27.02% as compared to squamous cell carcinoma 23.14%. Conclusion: PD-L1 expression is associated with increased aggressiveness, enhanced tumor progression and shorter survival in patients of NSCLC. This study concluded that frequency of positive immunohistochemical expression of PD-L1 in NSCLC is though low, yet significant in adenocarcinoma as compared to squamous cell carcinoma.